Fetal alcohol spectrum disorder and Risk-Need-Responsivity Model: A guide for criminal justice and forensic mental health professionals - Brown, Jerrod; Arvidson, Joe; Carter, Megan N.; Spiller, Vanessa (Frontiers in Psychology, 2023)
Fetal alcohol spectrum disorder (FASD) is an umbrella term used to describe a range of significant neurodevelopmental, brain-based disorders and impairments that can result from prenatal alcohol exposure. FASD is a high prevalence but under-diagnosed group of disorders affecting between 17-36% of individuals in criminal justice settings. Despite being a high-impact disorder associated with lifelong impairments with a significant need for services and interventions, little research has been completed on how to best support individuals with these conditions in criminal justice settings. This article proposes a renewed focus on applying and adapting the Risk-Need-Responsivity (RNR) approach to individuals with FASD in criminal justice settings. This will assist in better determining the needs and interventions likely to effect change and reduce recidivism for this prominent criminal justice-based population. The RNR approach has been used with multiple corrections populations to determine need and most appropriate interventions, as well as how to best allocate scarce resources. As the prevalence of FASD becomes better understood and recognized, evidence-based approaches to addressing this specific sub-population are necessary to effect change and reduce recidivism and ongoing involvement in the criminal justice system.